Composition Fractional Integral Inequality for the Reiman-Liouville type with applications - Hamasalh, Faraidun K.; Rasheed, Sudad M.; Muhammad, Pshtiwan O. (Sulaimani Journal for Pure and Applied Sciences, 2016)
In this work, some integral inequalities of fractional order of Riemann-Liouville type are established, which generalized some know inequalities for [8]. These can be used in the analysis of various problems in the theory of certain classes of fractional differential equations and fractional integral equations. Also, some applications for the fractional differential and integral equations are also indicated.
Keywords: Fractional integral inequalities; Holders inequality